Genetic Bases of Bicuspid Aortic Valve: The Contribution of Traditional and High-Throughput Sequencing Approaches on Research and Diagnosis - Giusti, Betti; Sticchi, Elena; De Cario, Rosina; Magi, Alberto; Nistri, Stefano; Pepe, Guglielmina (Frontiers in Physiology, 2017)
Bicuspid aortic valve (BAV) is a common (0.5-2.0% of general population) congenital heart defect with increased prevalence of aortic dilatation and dissection.BAV has an autosomal dominant inheritance with reduced penetrance and variable expressivity.BAV has been described as an isolated trait or associated with syndromic conditions [e.g. Marfan or Loeys-Dietz syndrome (MFS, LDS)].Identification of a syndromic condition in a BAV patient is clinically relevant to personalize aortic surgery indication.A 4-fold increase in BAV prevalence in a large cohort of unrelated MFS patients with respect to general population was reported, as well as in LDS patients (8-fold). It is also known that BAV is more frequent in patients with thoracic aortic aneurysm related to mutations in ACTA2, FBN1, and TGFBR2 genes. Moreover, in 8 patients with BAV and thoracic aortic dilation, not fulfilling the clinical criteria for MFS, FBN1 mutations in 2/8 patients were identified suggesting that FBN1 or other genes involved in syndromic conditions correlated to aortopathy could be involved in BAV. Beyond loci associated to syndromic disorders, studies in humans and animal models evidenced/suggested the role of further genes in non-syndromic BAV. The transcriptional regulator NOTCH1 has been associated with the development and acceleration of calcium deposition.Genome wide marker-based linkage analysis demonstrated a linkage of BAV to loci on chromosomes 18q, 5q and 13q. Recently, a role for GATA4/5 in aortic valve morphogenesis and endocardial cell differentiation has been reported. BAV has also been associated with a reduced UFD1L gene expression or involvement of a locus containing AXIN1/PDIA2.Much remains to be understood about the genetics of BAV.In the last years, high-throughput sequencing technologies, allowing the analysis of large number of genes or entire exomes or genomes, progressively became available.The latter issue together with the development of “BigData” analysis methods improving their interpretation and integration with clinical data represents a promising opportunity to increase the disease knowledge and diagnosis in monogenic and multifactorial complex traits.This review summarized the main knowledge on the BAV genetic bases, the role of genetic diagnosis in BAV patient managements and the crucial challenges for the comprehension of genetics of BAV in research and diagnosis.